RESEARCH ON DYNAMICS CHARACTERISTICS OF SPUR GEAR BASED ON DYNAMIC MSEH STIFFNESS - DAI ZhanSheng; LIU GuiMian (Jixie qiangdu)
The rotational speed of gear system directly affects the dynamic characteristies of gear system, but this important factor was often ignored by many scholars in the caleulation of mesh stiffness. In order to study the influence of rotational speed on mesh stiffness, an algorithm of calculating the dynamic mesh stiffness which related to rotational speed was proposed based on finite element framework by using the average acceleration method. Meanwhile, the dynamic mesh stiffness under different rotational speeds was simulated and analyzed. Finally, the relevant dynamic characteristics of gear system which affected by dynamic mesh stiffness were further explored. The research results show that the dynamic mesh stiffness varies with rotational speed of gear system. With the increase of rotational speed, the fluctuation range of the dynamic mesh stiffness increases relative to the static mesh stiffness. The resonance speed range of the gear system calculated by dynamic mesh stiffness is either ahead or behind the static mesh stiffness, and the super harmonic response of dynamie mesh stiffness model is more obvious at high rotational speed. The research on dynamic mesh stiffness related to rotational speed can provide reference for improving transmission performance and reducing vibration and noise of spur gear.